Individualized and multidisciplinary approach of syncope in the elderly: a case report - Correia,Sofia Oliveira (2019)
Syncope is a frequent reason for emergency room visits. In the elderly, multiple chronic conditions can difficult the diagnosis. In this case, an unexpected association between symptoms and the final diagnosis was a clinical challenge. An 80-year-old Caucasian man presents with syncopal episodes after a cough. Dizziness and visual changes were the only preceding complaints. Structured assessment is needed to face any patient, but is particularly important in the older patient because there are several constraints that hinder the approach: chronic diseases, different physiology, and clinical history sometimes more nonspecific. Thus, a diagnostic approach is discussed, with special focus in carotid sinus syndrome.